Online Marketing Strategy in the Perspective of Islamic Economics on Saye Stores - Ningsih, Yulita Futria; Daud, Daud; Sunarti, Zeni (Zabags International Journal of Economy, 2025)
This type of research is qualitative research with a descriptive approach. This research was conducted at Toko Saye (Rumah Oleh-Oleh Zhafira) Tanjung Solok Village, Kuala Jambi District. Data collection techniques are carried out through observation, interviews and documentation related to the title. The data analysis technique used is qualitative analysis and is presented in descriptive form. Based on the results of the discussion and analysis, conclusions were obtained: Toko Saye (Rumah Oleh-Oleh Zhafira) has implemented a marketing strategy with a 7P marketing mix, namely, product (product), price (price), distribution channel (place), promotion (promotion), people (people), process (process), physical facilities (physical evidence). However, the implementation is not fully maximized because in the promotion section Shopee Toko Saye (Rumah Oleh-Oleh Zhafira) does not carry out promotions as in 7P in the Shopee application, Toko Saye (Rumah Oleh-Oleh Zhafira) instead uses social media such as Instagram and Facebook as promotional media. Even though Shopee is the right media for selling with the right marketing. While in terms of the perspective of Islamic Economics, the 7P marketing mix that has been implemented by Toko Saye (Rumah Oleh-Oleh Zhafira) is in accordance with Islamic Economics based on the characteristics of the Prophet Muhammad Saw, namely fathanah, amanah, shiddiq, and tabligh. These four traits are the traits applied by the Prophet Muhammad.